Decision Support System, SAW Method, Best Journalist Selection, Harian Rakyat Bengkulu, Multi-Criteria Decision Making - Andriansyah, Andriansyah; Kanedi, Indra; Prahasti, Prahasti (Jurnal Media Computer Science, 2025)
The development of information technology has a significant impact on the world of journalism, including in efforts to improve the professionalism of journalists. PT. Rakyat Semarak Bengkulu Permai (Rakyat Bengkulu) as a press company continues to innovate, one of which is through periodic assessment of the best journalists. However, the assessment process that has been running so far still faces the obstacle of subjectivity and has not been supported by an objective and measurable system. This study aims to develop a web-based Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to help the journalist assessment process more efficiently and objectively. This system is built using the PHP programming language and MySQL database, and is specifically designed so that it can only be accessed by the Editor-in-Chief. The test results show that the system is able to improve efficiency, objectivity, and accuracy in the process of assessing the best journalists in the company environment